Bugtok disease of banana - Soguilon, C.E.; Magnaye, L.V.; Natural, M.P.; International Network for the Improvement of Banana and Plantain (1995)
Fact sheet on Bugtok disease of banana: bacterial identification, symptoms, pathogenesis, control.